THE IMPLEMENTATION OF QUESTIONING STRATEGY IN TEACHING SPEAKING FOR THE TENTH GRADE IN MA AL-ABROR BLUMBUNGAN PAMEKASAN - Ina Daril Hanna; Arisandi Setiyawan (Universitas Islam Lamongan, 2018)
Teaching speaking is an important part of language learning so that the English teacher should use some strategies to improve the students’ speaking skill. At the tenth grade of MA AL-ABROR Blumbungan Pamekasan, the English teacher used questioning strategy to encourage the students to be better in speaking.That is why the researchers want to describe the phenomena further in the research entitled the implementation of questioning strategy in teaching speaking for the tenth grade in MA AL-ABROR Blumbungan Pamekasan. The aim of this research was to find out how was the implementation of questioning strategy for the tenth grade in MA AL-ABROR Blumbungan Pamekasan, what types of the question were used by the teacher in the implementation of questioning strategy for the tenth grade in MA AL-ABROR Blumbungan Pamekasan,and how did the responses of thestudents in the implementation of questioning strategy for the tenth grade in MA AL-ABROR Blumbungan Pamekasan. The instruments used by the researchers answer observation, interview and documentation in collecting the data.The results were 1. the teacher used questioning strategy by using some steps in teaching speaking, the first step is deciding the topic related with the students’ environment, then He give some vocabullaries related to the topic. Then teacher choose some students who have low ability and medium or high ability in speaking to treat them in giving them both the convergent questions and divergent questions. The last The teacher use increasing wait-time when the students need time to think about the questions, 2.The teacher used convergent and divergent questions, it was done to make the students have better understanding in speaking and the students can be easy in answering the question given by the teacher. 3. The student’s responses in implementing of questioning strategy are various , they were comfort, nervous, afraid but They could enjoy it because the topic relate with their environment